Systematic Literature Riview (SLR): Implementasi Model Problem Based Learning (PBL) terhadap Kemampuan Koneksi Matematis Siswa - Fadilah, Choirunisa Fitri; Nindiasari, Hepsi; Novaliyosi, Novaliyosi; Mutaqqin, Anwar (ANARGYA: Jurnal Ilmiah Pendidikan Matematika, 2025)
The objective of this study is to identify, present, and analyze several primary studies concerning the implementation of the Problem-Based Learning (PBL) model in relation to students’ mathematical connection abilities. To support this investigation, the appropriate method employed is the Systematic Literature Review (SLR), which involves several stages: formulating research questions, collecting primary studies, applying inclusion criteria, and ultimately selecting 20 relevant articles. The selected primary studies were then evaluated and analyzed based on several categories, including educational level, instructional approaches employed, research methods, and the effectiveness of PBL in enhancing students’ mathematical connection skills. The evaluation and analysis reveal that the majority of the studies adopted a quantitative research method, particularly quasi-experimental designs, which demonstrate a positive impact of PBL on students’ mathematical connection abilities, especially at the junior high school level. However, most implementations of the PBL model were general in nature and did not incorporate varied instructional approaches. Therefore, there is a need for the integration of other pedagogical approaches that are closely aligned with PBL, such as the metacognitive approach, to optimize its effectiveness